Determinan Praktik Penghindaran Pajak - Santoso, Tiara Rani; Estrini, Dwi Hayu; Ariella, Vanessa Elvina (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2023)
The aim of this research is to prove the effect of sales growth, accounting conservatism and corporate risk on tax avoidance. CETR used in this research to count tax avoidance. This research uses quantitative research method secondary data in the form of financial statment of Food and Beverage Sub-sector listed in Indonesia Stock Exchange (IDX) from 2017-2021 period. Number of the sample used in this reseach is 80 samples obtained by purposive sampling method. The analysis technique used in this research is multiple linear regression analysis using SPSS 26 version. The result of this research shows that sales growth has negative effect on tax avoidance. Accounting conservatism and corporate risk have no effect on tax avoidance.